182 COMPARISON OF QUADRATIC AND CUBIC EQUILIBRIUM SOLUTIONS OF FREE CORTISOL FOR PREDICTION OF SALIVARY CORTISOL IN HEALTHY ELDERLY HUMAN SUBJECTS. Issue 1 (1st January 2007) - Chynoweth, J.; Dorin, R. I.; Qualls, C. R.; Waters, D.; Scariano, J.
Abstract : Purpose: Free cortisol is released into the serum compartment where it is in equilibrium with serum binding proteins, corticosteroid-binding globulin (CBG), and albumin. The distribution of serum cortisol among free, CBG-bound, and albumin-bound compartments is influenced by association and disassociation rate constants for CBG and albumin, the number of unoccupied protein binding sites, and concentrations of CBG and albumin. Free cortisol in serum or plasma is difficult to assay; thus, salivary cortisol has been proposed as an alternative measure of free cortisol. In this study, we sought to assess and compare numerical methods, using both quadratic (Coolens et al, 1987) and cubic (Keenan et al, 2004) equations to calculate serum free cortisol and compare these findings with salivary cortisol in healthy elderly subjects. Methods: Serum and saliva samples were collected from 45 healthy, elderly subjects at 0700 h as part of the New Mexico Aging study (UNM HRRC 01-023). The salivary cortisol and total cortisol were measured using radioimmunoassay and ultrasensitive chemiluminescence, respectively. Serum CBG was measured by radioimmunoassay and serum albumin was measured using a bromcresol green method (UNM RAC 51). The cubic equation implied by Keenan et al and the quadratic equation described by Coolens et al were used to calculate free cortisol using our measured values for total cortisol, total CBG, and total albumin. Calculated free cortisol, total cortisol, and CBG concentration were then compared to salivary cortisol using Pearson's and Spearman's correlations. Results: There was a significant linear correlation between salivary cortisol and free cortisol calculated using the cubic equation ( r = .377, p = .033) and Coolen's quadratic equation ( r = .416, p = .018). In addition, we noted a linear correlation between CBG concentration and total cortisol ( r = .441, p = .0049). Conclusion: Our data indicate that the free cortisol calculated using either quadratic or cubic equations is correlated significantly with salivary cortisol but that other variables appear to influence measured salivary cortisol concentration. We did not observe the previously reported correlation between total and salivary cortisol, which suggests that aging may influence the relative distribution of cortisol in serum or salivary compartments.